Arduino based arm rehabilitation assistive device - Ambar, R.; Ahmad, M. S.; Mohd Ali, A. M.; Abdul Jamil, M. M. (2011)
Arm rehabilitation process requires the patients to do repetitive physical exercises without knowing their improvement rate may result in loss of interest or de-motivated, thus the patients may struggle to complete rehabilitation process. This paper focuses on the design of arm rehabilitation monitoring device utilizing multi-sensors equipped with portable data logging capabilities. The sensors are connected to a patient portable main unit that acquires and elaborates signals and record it in SD card to store detail information regarding subject’s various range of motions. The system enables clinician to do remote monitoring and provide organized sets of data on daily basis every time the user do rehabilitation workout at home.